Analysis of the Use of Codon Pairs in the He Gene of the Isa Virus Shows a Correlation Between Bias in Hpr Codon-Pair Use and Mortality Rates Caused by the Virus - Spencer-Ossa, E; Tello-Reyes, M (2013)
Background: Segment 6 of the ISA virus codes for hemoagglutinin-esterase (HE). This segment is highly variable, with more than 26 variants identified. The major variation is observed in what is called the high polymorphism region (HPR). The role of the different HPR zones in the viral cycle or evolution remains unknown. However viruses that present the HPR0 are avirulent, while viruses with important deletions in this region have been responsible for outbreaks with high mortality rates. In this work, using bioinformatic tools, we examined the influence of different HPRs on the adaptation of HE genes to the host translational machinery and the relationship to observed virulence. Methods: Translational efficiency of HE genes and their HPR were estimated analyzing codon-pair bias (CPB), adaptation to host codon use (codon adaptation index - CAI) and the adaptation to available tRNAs (tAI). These values were correlated with reported mortality for the respective ISA virus and the ?G of RNA folding. tRNA abundance was inferred from tRNA gene numbers identified in the Salmo salar genome using tRNAScan-SE. Statistical correlation between data was performed using a non-parametric test. Results: We found that HPR0 contains zones with codon pairs of low frequency and low availability of tRNA with respect to salmon codon-pair usage, suggesting that HPR modifies HE translational efficiency. Although calculating tAI was impossible because one third of tRNAs (?60.000) were tRNA-ala, translational efficiency measured by CPB shows that as HPR size increases, the CPB value of the HE gene decreases (P = 2×10-7, ? = -0.675, n = 63) and that these values correlate positively with the mortality rates caused by the virus (? = 0.829, P = 2×10-7, n = 11). The mortality associated with different virus isolates or their corresponding HPR sizes were not related with the ?G of HPR RNA folding, suggesting that the secondary structure of HPR RNA does not modify virulence. Conclusions: Our results suggest that HPR size affects the efficiency of gene translation, which modulates the virulence of the virus by a mechanism similar to that observed in production of live attenuated vaccines through deoptimization of codon-pair usage. © 2013 Tello et al.; licensee BioMed Central Ltd.